Nur Kasih Homestay online booking system / Athirah Liyana Mohmad - Mohmad, Athirah Liyana (2013)
This research explain on how a web based application support booking process for homestay since this research tends to change people’s lifestyle by booking homestay using electronic devices. Studies on rapid prototyping lead us to a better flow in implementing a website for reserving homestay and make people believe that every step taken in booking process can help customers properly. The results of the research are holistically provides the usability of the proposed system and explain more in designing an online booking homestay. This research analysis is significant to offer variety in web based application relates to homestay reservation hence develop a supplementary source of income to its host and inexpensive alternative accommodation to customer.